Synthesis of New Mannich Bases from Indole Derivatives (Baghdad Science Journal, 2012)
This work includes two steps of synthesis, the first one is the synthesis of indole which was prepared according to literature of the reaction of phenyl hydrazine with acetaldehyde in glacial acetic acid afforded phenyl hydrazone of acetaldehyde , this product was fused with zinc chloride to give the indole.Reaction of cyclohexanone with phenyl hydrazine using the same procedure for the preparing giving 1,2,3,4-Tetrahydrocarbazole.Second step involved synthesis of a series of (17) of mannich bases derivatives of indole and 1,2,3,4-Tetrahydrocarbazle. Mannich reaction involves the condensation of aldehyde usually formaldehyde with different secondary amine and with compound containing an activated hydrogen.The reaction illustrated by the following equation :R2NH+HCHO+RH?R2N-CH2-R+H2O These compounds were characterized by U.V , FT-IR and 1H-NMR spectra for two compounds. The secondary amines that used to prepare mannich bases are:N-methyl –N-phenyl amine, N,N-dimethyl amine, N,N- diphenyl amine, N-ethyl –N- phenyl amine, N,N-di-n-propyl amine, pyrrolidine, morpholine, N- methyl pipyridine, N,N-dibenzyl amine, N,N-di –n-butyl amine and N,N-di ethyl amine.